Re: [isabelle] proof solution [ newbie question ]
I don't think it is provable for xs and ys empty.
lemma assumes xs0: "xs ~= " and ys0: "ys ~= " and hd: "hd xs = hd
ys" and tl: "tl xs @ zs = tl ys"
shows "xs @ zs = ys"
from xs0 ys0 obtain xsh xst ysh yst
where xs: "xs = xsh#xst" and ys: "ys = ysh#yst" apply (cases xs, auto)
apply (cases ys, auto) done
with hd have xsh: "xsh = ysh" by simp
have "ys = xsh#(tl ys)" by (simp add: ys xsh)
also have "... = xsh # xst @ zs" by (simp add: tl[symmetric] xs)
finally show ?thesis by (simp add: xs)
Gregory Kulczycki wrote:
I've been experimenting with the Isabelle prover and have reached a
a proof where I have the following subgoal:
/\ xs ys zs. [| hd xs = hd ys; tl xs @ zs = tl ys |] ==> xs @ zs = ys
This looks obvious to me (since xs @ zs = ys is equivalent to hd xs # tl xs
@ zs = hd ys # tl ys for non-empty xs) , but I don't know how to proceed.
This archive was generated by a fusion of
Pipermail (Mailman edition) and